(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Standardization of herbo-mineral drugs is essential to certify their quality, purity and reproducibility. Vishatindukadi Vati is a herbo-mineral formulation mentioned in Rasatantrasaara and Siddhaprayoga Sangraha (RTSSPS) with two references and different ingredients. The formulation mentioned in Gutika Prakarana contains Kupilu (Strychnos nux- vomica Linn), Maricha (Piper nigrum Linn.), Puga Phala (Araca catechu Linn.) and Chincha Beeja (Tamarindus indica Linn). while the formulation mentioned in Vatavyadhi Prakarana contains Kupilu (Strychnos nux-vomica Linn.) and Maricha (Piper nigrum Linn.) with Bhavana of Nagavalli (Piper betel Linn.) Patra Svarasa. It is mentioned in context of various diseases i.e., Jirna Vatavyadhi (chronic disorders due to Vata), Jirna Jvara (chronic fever), Ajirna (indigestion), Mandagni (subdued digestive power) and many more. In pharmaceutical process; 3 batches of Kupilu Shodhana and using both references three batches of Vishatindukadi Vati were prepared and its organoleptic and physico-chemical analysis were performed. Organoleptic and physicochemical analysis of raw materials, in-process and finished products were done. In physico-chemical pH, loss on drying at 105°C, total ash (%w/w), acid insoluble ash (%w/w), water-soluble extractive (%w/w), alcohol soluble extractive (%w/w), uniformity of weight (mg), friability (%), hardness (kg/cm2) and disintegration time (min.) were carried out for VTV1 and VTV2. An average value of VTV1 and VTV2 were 5.3, 6.48%, 1.55%, 0.24%, 22.5%, 6.96%, 124.3mg, 0.16%, 4.6kg/cm2, 37.6min and 5.05, 7.24%, 2.39%, 0.26%, 23.7%, 6.69%, 124mg, 0.14%, 3.63kg/cm2 and 32 min. respectively. It needs further preclinical and clinical studies to prove its safety profile and therapeutic efficacy.